Review of optimization techniques applied for the integration of distributed generation from renewable energy sources. (December 2017) - Abdmouleh, Zeineb; Gastli, Adel; Ben-Brahim, Lazhar; Haouari, Mohamed; Al-Emadi, Nasser Ahmed
Abstract: Several potential benefits to the quality and reliability of delivered power can be attained with the installation of distributed generation units. To take full advantage of these benefits, it is essential to place optimally sized distributed generation units at appropriate locations. Otherwise, their installation could provoke negative effects to power quality and system operation. Over the years, various powerful optimization tools were developed for optimal integration of distributed generation. Therefore, optimization techniques are continuously evolving and have been recently the focus of many new studies. This paper reviews recent optimization methods applied to solve the problem of placement and sizing of distributed generation units from renewable energy sources based on a classification of the most recent and highly cited papers. In addition, this paper analyses the environmental, economic, technological, technical, and regulatory drivers that have led to the growing interest on distributed generation integration in combination with an overview about the challenges to overcome. Finally, it examines all significant methods applying optimization techniques of the integration of distributed generation from renewable energy sources. A summary of common heuristic optimization algorithms with Pro-Con lists are discussed in order to raise new potential tracks of hybrid methods that haven't been explored yet. Highlights: Review of recent papers about optimization techniques applied to solve the problem of placement and sizing of DGs from RES. Drivers that have led to the growing interest on DGs integration and the challenges to overcome are analyzed. A summary of common heuristic optimization algorithms with their Pro-Cons are discussed. New possible hybrid optimization methods were identified which might lead to better solutions and improvements. This survey is an essential guideline for the future research and enhancement on optimal DG placement and sizing.